Mode of delivery and childhood fractional exhaled nitric oxide, interrupter resistance and asthma: the Generation R study. Issue 4 (June 2015) - van Berkel, Annemaria C.; den Dekker, Herman T.; Jaddoe, Vincent W. V.; Reiss, Irwin K.; Gaillard, Romy; Hofman, Albert; de Jongste, Johan C.; Duijts, Liesbeth
Abstract Background Previous studies suggest that caesarean section may influence the risk of childhood asthma. We examined the associations of different modes of delivery with childhood wheezing patterns, asthma, fractional exhaled nitric oxide (FeNO) and airway interrupter resistance (Rint) up to school age. Methods This study among 6, 128 children was embedded in a population‐based prospective cohort study. Information on mode of delivery was obtained from midwives and hospital registries. Wheezing patterns from birth onwards and ever physician‐diagnosed asthma at age 6 yr were assessed by questionnaires. FeNO and Rint were measured at age 6 yr. We used multivariate polynomial, logistic and linear regression models. Results Compared with vaginal delivery, caesarean section was associated with increased risks of early and persistent wheezing up to school age [odds ratios (95% confidence interval): 1.36 (1.06, 1.75) and 1.73 (1.24, 2.40), respectively]. The effect sizes of elective and emergency caesarean section with wheezing outcomes were similar. Only elective caesarean section was associated with a higher FeNO level [sympercent (95% CI): 12.7 (0.6, 24.8)]. We did not observe associations of mode of delivery with asthma or Rint. Also, vacuum‐ or forceps‐assisted vaginal delivery was not associated with any asthma or related outcome. Conclusions Both elective and emergency caesarean sections are associated with increased risks of early and persistent wheezing up to school age. This might be explained by increased airway inflammation reflected by higher FeNO levels.